Serum Ferritin Status of Patients with Type 2 DM Attending OPD of BIRDEM General Hospital - Begum, Khadiza; Islam, Fahmida; Aktar, Farjana; Aziz, Murshida; Tahiya, Tohfa E Ayub (Anwer Khan Modern Medical College Journal, 2020)
Background: In recent times much is talked about of serum ferritin, an acute phase reactant a marker of iron stores in the body and its association with diabetes mellitus. Studies implicate that increased body iron stores and subclinical hemochromatosis has been associated with the development of glucose intolerance, type 2 diabetes and its micro as well as macrovascular complications. Material & Methods: This study was carried out to examine and to observe for any relationship between serum ferritin with Type 2 diabetes mellitus. Our study populations were included 163. Among them 81 type 2 diabetes patients as a case (M=49,F=32, mean 44.68 age in years)and 82 normal healthy individual as a control ( M=35, F=47 , mean 34.71 in years). Results: Majority were healthy outpatients who had come for regular checkup and were matched with controls. Serum ferritin and FBS were estimated and other investigations. Results showed that although Serum ferritin was in the normal range value it was increased in type 2 diabetes patients than in controls and was statistically significant, we did get a positive correlation with duration of diabetes. It can be concluded that there were positive associations between serum ferritin and FBG, age, sex among study groups. Conclusion: In conclusion our study shows that there is significant correlation between increased serum ferritin in diabetes compared to individuals with normal blood sugars in this part and hyper ferritinemia may be one of the causes for development of insulin resistance before overt diabetes. Anwer Khan Modern Medical College Journal Vol. 11, No. 1: Jan 2020, P 7-10